Balancing the Selective Absorption and Photon‐to‐Electron Conversion for Semitransparent Organic Photovoltaics with 5.0% Light‐Utilization Efficiency. Issue 41 (11th September 2022) - Guan, Shitao; Li, Yaokai; Yan, Kangrong; Fu, Weifei; Zuo, Lijian; Chen, Hongzheng
Abstract: Efficiently converting invisible light while allowing full visible light transmission is key to achieving high‐performance semitransparent organic photovoltaics (ST‐OPVs). Here, a detailed balance strategy is explored to optimize the ST‐OPV via taking both absorption and carrier dynamics into consideration. Based on this principle, comprehensive optimizations are carried out, including a ternary strategy, donor:acceptor blend ratio, thickness, antireflection, etc., to compromise the invisible energy conversion and visible transmission for high‐performance ST‐OPVs. As a result, the opaque OPV device exhibits a champion power conversion efficiency of 19.35% (certificated 19.07%), and most strikingly, the best ST‐OPV shows a remarkably high light‐utilization efficiency of 5.0%, where the efficiency and the average visible transmission are 12.95% and 38.67%, respectively. An efficiency of 12.09% is achieved on the upscaled device with an area of 1.05 cm 2, demonstrating its promise for large‐area fabrication. These results are among the best values for ST‐OPVs. Besides, it is demonstrated that the ST‐OPV exhibits good infrared light‐reflection capability for thermal control. This work provides a rational design of balancing the absorbing selectivity and photon‐to‐electron conversion for high‐performance ST‐OPVs, and may pave the way toward the practical application of solar windows. Abstract : Balancing the selective absorption and photon‐to‐electron conversion is key to achieving high‐performance semitransparent organic photovoltaics (ST‐OPVs). Following this, ST‐OPV with a high light‐utilization efficiency of 5.0% is reached via comprehensive optimization on materials, active layers, and device structures. Furthermore, the ST‐OPV exhibits good upscaling and thermal control ability, representing a promising candidate adaptive to versatile applications.